Acaricidal Properties of Bio-Oil Derived From Slow Pyrolysis of Crambe abyssinica Fruit Against the Cattle Tick Rhipicephalus microplus (Acari: Ixodidae) - Mattos, Camila; Andrade, Juliana; Salarini Peixoto, Bruno; Tavares Moraes, Nayara Luiza; da Cunha Veloso, Marcia Cristina; Alves Romeiro, Gilberto; Folly, Evelize das Chagas (Frontiers in Physiology, 2021)
Slow pyrolysis is a process for the thermochemical conversion of biomasses into bio-oils that may contain a rich chemical composition with biotechnological potential. Bio-oil produced from crambe fruits was investigated as to their acaricidal effect. Slow pyrolysis of crambe fruits was performed in a batch reactor at 400°C and chemical composition was analyzed by gas chromatography-mass spectrometry (GC-MS). The bio-oil collected was used in bioassays with larvae and engorged females of the cattle tick Rhipicephalus microplus. Biological assays were performed using the larval packet test (LPT) and adult immersion test. The GC-MS of crambe fruit bio-oil revealed mainly hydrocarbons such as alkanes and alkenes, phenols, and aldehydes. The bio-oil in the LPT exhibited an LC90 of 14.4%. In addition, crambe bio-oil caused female mortality of 91.1% at a concentration of 15% and a high egg-laying inhibition. After ovary dissection of treated females, a significant reduction in gonadosomatic index was observed, indicating that bio-oil interfered in tick oogenesis. Considering these results, it may be concluded that slow pyrolysis of crambe fruit affords a sustainable and eco-friendly product for the control of cattle tick R. microplus.